VOICES OF PRE-SERVICE ENGLISH TEACHERS: REFLECTING MOTIVATIONS DURING PRACTICUM LEARNING - Paulus Kuswandono (TEFLIN, 2014)
After Dewey (1933) and SchoÌn (1983, 1987), education scholars began to look further at the concepts of reflection for learning. Following these concepts, there have been plenty of studies on reflection, particularly those discussing teachers’ classroom experiences and their endeavour to develop professional skills. However, educational practitioners in Indonesia (as in the rest of the world) often criticise preservice teachers’ (PSTs) lack of content knowledge, which they claim should be ‘prioritised’ during a teacher education course. Such pressing situations may have made it difficult to model or experience reflective practice. Against these odds, this research paper addresses issues related to the identity and professional development of thirteen English PSTs during their campus and school-based practicum in an Indonesian university. This study collected empirical data through PSTs’ reflective journals, questionnaires, individual interviews, focus group discussion, and autobiography. The study examines problems encountered by PSTs, namely their motivations to become teachers. This study signifies that teacher education needs to provide more reflective dialogues to shape PSTs’ identity and professionalism.